File concepts for parallel I/O - Crockett, T. W. (Proceedings of the 1989 ACM/IEEE conference on Supercomputing, 1989)
The subject of I/O has often been neglected in the design of parallel computer systems, although for many problems I/O rates will limit the speedup attainable. The I/O problem is addressed here by considering the role of files in parallel systems. The notion of parallel files is introduced. Parallel files provide for concurrent access by multiple processes, and utilize parallelism in the I/O system to improve performance. Parallel files can also be used conventionally by sequential programs. A set of standard parallel file organizations is proposed, based on common data partitioning techniques. Implementation strategies for the proposed organizations are suggested, using multiple storage devices. Problem areas are also identified and discussed.